Direct superior approach with standard instrumentation for total hip arthroplasty: safety and efficacy in a prospective 200-case series. Issue 5 (September 2020) - Tsiridis, Eleftherios; Kenanidis, Eustathios; Potoupnis, Michael; Sayegh, Fares E
Introduction: Direct Superior Approach (DSA) is a muscle sparing approach for total hip arthroplasty (THA) implemented using special instrumentation. There is a lack of information in the literature concerning DSA with standard instrumentation. Materials and methods: 238 patients were recruited for primary THA by a single surgeon from January 2016 until May 2017. 209 patients underwent THA through DSA approach with non-offset acetabular reamers and femoral broaches. We evaluated accuracy of implantation, complications and early functional results. Independent orthopaedic surgeons performed the clinical and radiographic assessments. Results: 200 patients were followed for a year. 3 different implants were used. No sciatic nerve palsies, hip dislocations or fractures were recorded. There was one acute deep and superficial wound infection. The mean functional score was significantly improved at all follow-ups ( p < 0.001). 97% of stems were inserted into the neutral coronal and 96% in neutral sagittal alignment. All cups fell within a safe zone of inclination and 91% of anteversion. 2 hips demonstrated heterotopic ossification, Brooker class I. Obese patients had no increased risk of complications. Conclusions: DSA with standard instrumentation is safe and efficacious for THA. It offers fast recovery and facilitates correct implantation of different implants, can be useful even for hip dysplasia and obese patients with minimal complication rates.